A Genetic Screen Reveals Novel Targets to Render Pseudomonas aeruginosa Sensitive to Lysozyme and Cell Wall-Targeting Antibiotics - Lee, Kang-Mu; Lee, Keehoon; Go, Junhyeok; Park, In Ho; Shin, Jeon-Soo; Choi, Jae Young; Kim, Hyun Jik; Yoon, Sang Sun (Frontiers in Cellular and Infection Microbiology, 2017)
Pseudomonas aeruginosa is capable of establishing airway infections. Human airway mucus contains a large amount of lysozyme, which hydrolyzes bacterial cell walls. P. aeruginosa, however, is known to be resistant to lysozyme. Here, we performed a genetic screen using a mutant library of PAO1, a prototype P. aeruginosa strain, and identified two mutants (ΔbamB and ΔfabY) that exhibited decrease in survival after lysozyme treatment. The bamB and fabY genes encode an outer membrane assembly protein and a fatty acid synthesis enzyme, respectively. These two mutants displayed retarded growth in the airway mucus secretion (AMS). In addition, these mutants exhibited reduced virulence and compromised survival fitness in two different in vivo infection models. The mutants also showed susceptibility to several antibiotics. Especially, ΔbamB mutant was very sensitive to vancomycin, ampicillin, and ceftazidime that target cell wall synthesis. The ΔfabY displayed compromised membrane integrity. In conclusion, this study uncovered a common aspect of two different P. aeruginosa mutants with pleiotropic phenotypes, and suggests that BamB and FabY could be novel potential drug targets for the treatment of P. aeruginosa infection.